2016
DOI: 10.1093/mnras/stw2813
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term evolution of a stellar disc around a massive black hole: the role of the cusp, stellar evolution and binaries

Abstract: We study the dynamical evolution of a stellar disk orbiting a massive black hole. We explore the role of two-body relaxation, mass segregation, stellar evolution and binary heating in affecting the disk evolution, and consider the impact of the nuclear cluster structure and the stellar-disk mass-function. We use analytic arguments and numerical calculations, and apply them to study the evolution of a stellar disk (similar to that observed in the Galactic center; GC), both on the short (few Myr) and longer (100… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
(91 reference statements)
1
4
0
Order By: Relevance
“…Our simulations confirm the results of previous models in the case of the evolution of an isolated (no NSC) stellar disk (e.g. (Alexander et al 2007;Šubr & Haas 2014;Mikhaloff & Perets 2017) and references therein), showing only a steady disk-height increase over its 6 Myrs evolution, consistent with 2-body relaxation models. Such models produce a smooth (no clumps or asymmetries), aligned (no warping) structure which does not change its orientation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Our simulations confirm the results of previous models in the case of the evolution of an isolated (no NSC) stellar disk (e.g. (Alexander et al 2007;Šubr & Haas 2014;Mikhaloff & Perets 2017) and references therein), showing only a steady disk-height increase over its 6 Myrs evolution, consistent with 2-body relaxation models. Such models produce a smooth (no clumps or asymmetries), aligned (no warping) structure which does not change its orientation.…”
Section: Resultssupporting
confidence: 90%
“…Such processes kinematically heat the disk (i.e. increase the velocity dispersion of the disk stars), leading to higher eccentricities and disk thickening (Alexander et al 2007;Mikhaloff & Perets 2017;Naoz et al 2018), but are not expected to produce any of the aforementioned peculiar kinetic features (clumping, warping, asymmetries). The clump has been suggested to result from an IMBH residing in the disk; however, detailed kinematic studies of IRS13 ruled out the existence of such object (Maillard et al 2004;Genzel et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mass segregation is wellunderstood in spherical clusters (e.g. AH09; Bahcall & Wolf 1977;Spitzer 1987) and in axisymmetric disks (Alexander et al 2007;Mikhaloff & Perets 2017), but this is the first time that mass segregation has been explored in an eccentric disk with apsidally aligned orbits. AH09 studied mass segregation in an sphericallysymmetric, isotropic star cluster around an SMBH using Fokker-Planck methods.…”
Section: Radial Mass Segregationmentioning
confidence: 99%
“…Vertical mass segregation is a similar process to radial mass segregation, by which heavy stars sink to low inclinations while scattering light stars to high inclinations. It has been studied in the context of axisymmetric stellar disks around SMBHs (Alexander et al 2007;Mikhaloff & Perets 2017). They showed that in such systems, the scale height of the disk decreases with stellar mass due to two-body relaxation.…”
Section: Vertical Mass Segregationmentioning
confidence: 99%
See 1 more Smart Citation